PENGARUH EDUKASI KESEHATAN TERHADAP TINGKAT PENGETAHUAN MASYARAKAT TENTANG TUBERCULOSIS PARU - Lukita, Yenni; Renita, Renita; Erwhani, Indri (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Chronic diseases such as tuberculosis (TB) which is a disease with a fairly high incidence rate and is one of the causes of death in the world. World Health Organization (WHO) data in 2021 revealed that TB is the 13th cause of death and the second infectious killer after Covid-19. The purpose of this study was to determine the effect of health education on the level of public knowledge about tuberculosis in the Ledo District Health Center Work Area. This research method uses a quasi-experiment with a one group pretest-posttest design, without a comparison group (control) which was carried out on a population of 1323 people with a sample of 93 people selected using a random sampling technique conducted in September-December 2023. The results of this study found that most respondents were on average <39 years old (51.6%), female (73.1%) with high school education (41.9%). Researchers found that before the education was conducted, they had quite good knowledge (51.6%) and after the education, knowledge increased to good (55.9%), with a p value = 0.000. The conclusion of this study is that there is an influence of health education on the level of public knowledge about tuberculosis. Therefore, it is expected that through education with leaflet media and lecture methods, the level of public knowledge about pulmonary tuberculosis will increase.